House finches learn canary trills. Issue 2 (4th March 2021) - Mann, Dan C.; Lahti, David C.; Waddick, Laura; Mundinger, Paul C.
ABSTRACT: We analyse data from a cross-fostering experiment in which house finches were fostered by canary parents. Some individuals received canary song input, while others received no input, after a period of masking noise. We compare audio recordings of songs by these individuals to each other and to species-typical house finch and canary songs. Canary-tutored house finches learn to trill as part of their song. Since trills are not present in typical house finch song, naturally occurring song patterns underestimate what a species is capable of learning and producing. These results highlight a potential avenue for the origin of novel syntax in songbirds.